Coagulopathy reversal in intracerebral haemorrhage. Issue 1 (20th February 2020) - Sweidan, Alexander Jacob; Singh, Navneet Kaur; Conovaloff, Joseph Luke; Bower, Matthew; Groysman, Leonid I; Shafie, Mohammad; Yu, Wengui
Abstract : As intracerebral hemorrahge becomes more frequent as a result of an aging population with greater comorbidities, rapid identification and reversal of precipitators becomes increasingly paramount. The aformentioned population will ever more likely be on some form of anticoagulant therapy. Understanding the mechanisms of these agents and means by which to reverse them early on is critical in managing the acute intracerebral hemorrhage.